Dictionary of race and ethnic relations - Cashmore, Ernest (Routledge reference, 1996)
"Since the 1994 publication of the third edition of this acclaimed reference book there have been enormous changes in the area of race and ethnic relations throughout the world. The Dictionary of Race and Ethnic Relations deals with these changes through in depth articles which both define and analyze the terms. For this edition, there has been a total revision of existing entries and many new entries take account of developments in society and intellectual trends."--BOOK JACKET.